2020
DOI: 10.3892/etm.2020.8755
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin attenuates lipopolysaccharide‑induced cardiac dysfunction by inhibiting inflammation and regulating autophagy

Abstract: Ulinastatin exerts protective effects against lipopolysaccharide (LPS)-induced cardiac dysfunction. Autophagy has been demonstrated to serve an important role in sepsis-induced cardiomyopathy; however, whether ulinastatin has an anti-autophagic effect in sepsis requires further investigation. The present study aimed to determine the protective effects of ulinastatin on cardiac dysfunction and its role in autophagy during sepsis. C57BL/6J mice were randomly divided into a control, LPS and LPS + ulinastatin grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Due to these modulations, the LPS-induced model is excellent for the screening and subsequent evaluation of potential drugs or natural products on the inflammatory pathway [ 79 ]. LPS induction causes endotoxemia, which is related to a significant increase in cardiac dysfunction [ 80 ], triggered via toll-like receptor 4 (TLR-4)-mediated inflammatory responses. The trigger leads to a chronic low-grade pro-inflammatory condition, namely, metabolic endotoxemia (ME), which is usually high in CVD patients [ 81 ] Following administration of SQ at 25 and 50 µM for 18 h, the in vitro study conducted by Cardeno et al (2015), demonstrated attenuation in the inflammatory events caused by the LPS induction ( Table 2 ) [ 57 ].…”
Section: Anti-inflammatory Actions Of Squalenementioning
confidence: 99%
“…Due to these modulations, the LPS-induced model is excellent for the screening and subsequent evaluation of potential drugs or natural products on the inflammatory pathway [ 79 ]. LPS induction causes endotoxemia, which is related to a significant increase in cardiac dysfunction [ 80 ], triggered via toll-like receptor 4 (TLR-4)-mediated inflammatory responses. The trigger leads to a chronic low-grade pro-inflammatory condition, namely, metabolic endotoxemia (ME), which is usually high in CVD patients [ 81 ] Following administration of SQ at 25 and 50 µM for 18 h, the in vitro study conducted by Cardeno et al (2015), demonstrated attenuation in the inflammatory events caused by the LPS induction ( Table 2 ) [ 57 ].…”
Section: Anti-inflammatory Actions Of Squalenementioning
confidence: 99%
“…Previous studies have shown that ulinastatin inhibits autophagy, and in myocardial IR injury, ulinastatin exhibits a myocardial protective effect against IR injury, but ulinastatin was found to downregulate the LC3-II protein expression [38]. Ulinastatin exerts protective effects against lipopolysaccharide-induced cardiac dysfunction, and may be associated with its anti-in ammatory and anti-autophagic activity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations suggest that appropriate autophagy modulation has a potential role to improve cardiac function by regulating mitochondria and attenuating in ammation in SIC; moreover, the role of autophagy during the pathogenesis of sepsis has been under intensive exploration in recent years [62,65,66]. Previous studies have shown that multiple medicine and bioactive molecules exert cardioprotective effects by regulating autophagy in sepsis [70][71][72][73][74][75]. In this study, we explored the potential role of JuA in SIC.…”
Section: Discussionmentioning
confidence: 99%